Experimental investigations of palm oil based associative with petrol on performance and emission of four stroke engine / Junaidah Md Saad, Baljit Singh and P.A. Aswatha Narayana - Md Saad, Junaidah; Singh, Baljit; Narayana, P.A. Aswatha (Faculty of Mechanical Engineering (FKM) and UiTM Press, 2011)
This work investigates the effect of using palm oil based additive on four stroke engine performance and exhaust emission. This investigation focused on the comparison of performances of an internal combustion engine fitted with the fuel additive. Performance tests were conducted for, fuel consumption, engine torque and engine power, while exhaust emissions were analyzed for carbon monoxide (CO), carbon dioxide (CO₂), oxygen (O₂) and unburned hydrocarbons (HC) at variable engine speed ranging from 1000 to 6000 rpm. The results showed that the effect of the adding fuel addictive gives more power and increases fuel efficiency compared to the fuel without additives.